2013
DOI: 10.1155/2013/956878
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Soluble HLA-E and HLA-F at Diagnosis May Predict Overall Survival of Neuroblastoma Patients

Abstract: The purpose of this study was to identify the plasma/serum biomarkers that are able to predict overall survival (OS) of neuroblastoma (NB) patients. Concentration of soluble (s) biomarkers was evaluated in plasma (sHLA-E, sHLA-F, chromogranin, and B7H3) or serum (calprotectin) samples from NB patients or healthy children. The levels of biomarkers that were significantly higher in NB patients were then analyzed considering localized or metastatic subsets. Finally, biomarkers that were significantly different in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 28 publications
2
36
1
Order By: Relevance
“…However, that study did not determine whether sHLA-E is released by tumor cells or the immune cells involved in anti-tumor immunity [20]. Our study seemed to have the opposite result.…”
Section: Discussioncontrasting
confidence: 57%
“…However, that study did not determine whether sHLA-E is released by tumor cells or the immune cells involved in anti-tumor immunity [20]. Our study seemed to have the opposite result.…”
Section: Discussioncontrasting
confidence: 57%
“…Other investigations have been reported in the literature evaluating calprotectin concentrations in patients with appendicitis, 94,95 congestive heart failure, 96 and others. [97][98][99][100][101] Results did not show significant clinical impact other than increased levels compared to control groups. We speculate that part of the reason why some of these studies have not shown greater merit or have not been followed up with additional investigations is that there has not been the same degree of development, in terms of performance of analytical kits, for serum/plasma and/or urine samples compared to fecal specimens.…”
Section: Comparison To Other Serum/plasma Markersmentioning
confidence: 99%
“…Like HLA-Ia, HLA-E occurs on the surface of cells as a trimolecular complex comprised of HLA-E heavy chain, β2-microglobulin (β2m) and a peptide. In addition, HLA-E can be released into the microenvironment of the allograft and in circulation as soluble HLA (sHLA)-E [32,33]. In contrast to HLA-Ia, HLA-E binds to a restricted set of peptides, commonly derived from the leader sequence of HLA-Ia and HLA-G molecules [34][35][36]; it can also bind to viral, bacterial and stress protein-derived peptides [15,19,37].…”
Section: Hla-ementioning
confidence: 99%
“…Although HLA-F associates with β2m [48], no information is available on peptide presentation. It is thought to be biologically similar to other HLAIb molecules, such as in pregnancy [29,30] and cancer [32,49]; HLA-F also occurs in circulation as sHLA-F [32] like other sHLA-I molecules. However, the exact function of HLA-F remains to be elucidated.…”
Section: Hla-fmentioning
confidence: 99%
See 1 more Smart Citation